2012
DOI: 10.1083/jcb.201111115
|View full text |Cite
|
Sign up to set email alerts
|

The dynamin-like GTPase Sey1p mediates homotypic ER fusion in S. cerevisiae

Abstract: Budding yeast Sey1p functions analogously to mammalian atlastins in mediating ER fusion through a mechanism that is redundant with a second, ER SNARE-mediated fusion mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
162
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 103 publications
(172 citation statements)
references
References 27 publications
10
162
0
Order By: Relevance
“…Nonbranched ER tubules are also observed on expression of dominant-negative ATL mutants (8,12). In addition, the fusion of ER vesicles in Xenopus laevis egg extracts is prevented by ATL antibodies or a cytosolic fragment of ATL (8,15), and the fusion of the ER in mating yeast cells is delayed on SEY1 deletion (16). Most convincingly, proteoliposomes containing purified ATL, Sey1p, or RHD3 undergo GTP-dependent fusion in vitro (9,13,16,17).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Nonbranched ER tubules are also observed on expression of dominant-negative ATL mutants (8,12). In addition, the fusion of ER vesicles in Xenopus laevis egg extracts is prevented by ATL antibodies or a cytosolic fragment of ATL (8,15), and the fusion of the ER in mating yeast cells is delayed on SEY1 deletion (16). Most convincingly, proteoliposomes containing purified ATL, Sey1p, or RHD3 undergo GTP-dependent fusion in vitro (9,13,16,17).…”
mentioning
confidence: 67%
“…In addition, the fusion of ER vesicles in Xenopus laevis egg extracts is prevented by ATL antibodies or a cytosolic fragment of ATL (8,15), and the fusion of the ER in mating yeast cells is delayed on SEY1 deletion (16). Most convincingly, proteoliposomes containing purified ATL, Sey1p, or RHD3 undergo GTP-dependent fusion in vitro (9,13,16,17). Defects in ATL-mediated ER fusion can cause hereditary spastic paraplegia, a neurodegenerative disease characterized by the shortening of the axons in corticospinal motor neurons, leading to progressive spasticity and weakness of the lower limbs (13,18).…”
mentioning
confidence: 99%
“…Cells missing Sey1p and either Rtn1p or Yop1p have a reduced number of ER tubules, although cells missing only Rtn1p or Yop1p do not, indicating that Sey1p plays a role in maintaining ER tubules . Like atlastins, Sey1p also mediates homotypic ER fusion (Anwar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies illustrate that the addition of recombinant Rab GDI reduces the efficiency of ER network formation in vitro, presumably by disrupting the membrane association of all Rab proteins (Turner et al 1997;Audhya et al 2007). Notably, no Rab protein has been identified that localizes specifically to the ER and affects ER fusion, morphology or dynamics; however, a Rab-interacting SNARE protein, yeast Ufe1, has previously been implicated in ER assembly and provides more evidence for the involvement of a Rab GTPase in ER assembly (Patel et al 1998;Anwar et al 2012). …”
Section: Er Dynamics and Assemblymentioning
confidence: 99%
“…The factors that regulate homotypic ER membrane fusion must also be ER-specific, this is important because the ER is closely apposed and potentially tethered to nearly every membranebound compartment in the cell. Homotypic ER fusion is regulated by the Atlastin family of dynamin-like GTPases (Rismanchi et al 2008;Hu et al 2009;Orso et al 2009;Anwar et al 2012). Atlastin family members localize to the tubular ER and accumulate in a striking pattern at three-way junctions (Fig.…”
Section: Er Dynamics and Assemblymentioning
confidence: 99%